2007
DOI: 10.1007/s12149-007-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the serum IL-2R level and Ga-67 scan findings in making a differential diagnosis between sarcoidosis and non-Hodgkin's lymphoma

Abstract: Measurement of sIL-2R levels was sometimes useful in differentiating between sarcoidosis and stage III/IV non-Hodgkin's lymphoma, staging non-Hodgkin's lymphoma, and predicting the presence of the panda and/or lambda sign in sarcoidosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In line with previous works, we found that serum sIL‐2R levels were significantly higher than normal in patients with sarcoidosis (Fig. ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous works, we found that serum sIL‐2R levels were significantly higher than normal in patients with sarcoidosis (Fig. ).…”
Section: Discussionsupporting
confidence: 92%
“…Soluble interleukin‐2 receptor (sIL‐2R) is a 55‐kDa protein released mainly by activated T lymphocytes; therefore, levels of sIL‐2R have been considered to be a marker of T‐cell activation . In sarcoidosis, increased levels of sIL‐2R in serum and bronchoalveolar lavage fluid (BALF) have been reported, and serum levels of sIL‐2R were correlated with various indices of disease severity, including angiotensin‐converting enzyme (ACE), radiographic stage of disease, gallium‐67 ( 67 Ga) scintigraphy uptake and CD4 + T‐lymphocyte number in BALF…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous injection, it attaches to cells with transferrin receptors, such as macrophages and malignant cells. When used for the diagnosis of sarcoidosis, it is highly specific when multiorgan involvement is present, such as lymph nodes, lung and salivary glands 72. An abnormal gallium scan is a major diagnostic criterion for cardiac sarcoidosis, the intensity of uptake reflecting the degree of inflammation 73.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…It has also been used for monitoring response to therapy 75 76. Despite its advantages, gallium 67 scintigraphy is now less widely used because of its lower sensitivity,72 the difficulty of localising abnormalities unless coupled with SPECT-CT and a relatively high radiation burden of up to 15 mSv.…”
Section: Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation